Energy Audit and Waste Heat Recovery System Design for a Cement Rotary Kiln in Ethiopia: A Case Study - T. T., Ayu; M. H., Hailu; Hagos, F. Y.; Atnaw, Samson M. (Universiti Malaysia Pahang, 2015)
This paper deals with the energy audit and heat recovery system modeling and design , taking a cement factory in Ethiopia as a case study. The system is a dry type rotary kiln equipped with a sixth stage cyclone type preheater , pre - calciner and grate cooler. The kiln has a capacity of 3 , 000 tons/day. The energy auditing has been performed based on the data collected from control volume of the kiln system for a ten - month period . The result shows that 25.23% of the total heat input is released to the environment through the preheater and an other 15.58% through the cooler exhausts. The west heat recovery system (WHRS) can produce a gross power of 5.26 MW as long as the kiln is i n operation . The generated power can cover all the electrical energy consumption of the kiln system whether there is a power supply from the grid or not. Therefore, the company can save up to 536,222.10 USD per year due to the production of clinker using their own power source and avoiding the loss sustained by the company due to power interruption from the grid